The associations of cumulative adverse childhood experiences and irritability with mental disorders in detained male adolescent offenders. Issue 1 (December 2016) - Bielas, Hannes; Barra, Steffen; Skrivanek, Christine; Aebi, Marcel; Steinhausen, Hans-Christoph; Bessler, Cornelia; Plattner, Belinda
Abstract Background Adverse childhood experiences (ACEs) and psychiatric disorders are common in juvenile detainees. Emotional dysregulation resulting from cumulated ACEs may be characterized by symptoms of irritability. The present study examined whether the accumulation of ACEs, irritability, or both predicted mental disorders in incarcerated adolescents with and without controlling for one another and for socio-demographic factors. Methods One hundred thirty male detained juvenile offenders (aged 13.8–19.5 years) were assessed by structured clinical interviews and a self-reporting scale for irritability. Univariate and multivariate regression models were used to examine the shared and distinct associations of ACEs and irritability with psychiatric diagnoses. Results A total of 75 % of the participants reported more than one ACE. The ACE total score was positively related to self-reported irritability. The ACE total score predicted depressive disorders, suicidality, post-traumatic stress disorder (PTSD), and anxiety disorders. Irritability was positively related to depressive disorders, suicidality, disruptive behavior disorder (DBD), substance use disorder (SUD), and attention deficit hyperactivity disorder (ADHD). These associations remained significant in multivariate models. Conclusions This study provides evidence for the predictive impact of self-reported ACEs and irritability with regard to adolescent psychiatric disorders in young male inmates. Both variables differed in their predictive power for PTSD, internalizing, and externalizing disorders indicating the need for specific therapeutic interventions. Taking a close look at their trauma history seems to be of special importance for juveniles suffering from PTSD and anxiety disorders. For delinquent adolescents with DBD, ADHD and SUD, the training of emotion regulation techniques appears most promising. Approaches focusing on both, ACEs and emotion-focused contents may be implemented in the treatment of depressive disorders and suicidality.